Investigation of quality of life in the treatment of locally advanced and recurrent oropharyngeal cancer: State-of the-art - D. V. Sikorsky; S. O. Podvyaznikov (Опухоли головы и шеи)
Postsurgical survival is considered to be indicators of treatment efficiency in most cases. However, the sociomedical rehabilitation of patients in this group is no less important; not only life expectancy, but also functional rehabilitation and quality of life are in the lead in patients with Stage III–IVA due to their low 2-year and much lower 5-year survival. The main efficiency criterion is patients, quality of life as compared to antitumor treatment programs in the absence of differences in survival.As the only chance of cure or life prolongation in most cases, multicomponent surgery for locally advanced and recurrent oropharyngeal cancer may be refused by a patient for fear of being lost to society. Identification of surgical treatment-induced changes in quality of life in patients may be used as a criterion for assessing the performed operations.The body's changes in a patient with otopharyngeal cancer are associated with impairment of basic physiological functions (deglutition, mastication, and breathing), sensitivity (taste, olfaction, and hearing), and individual characteristics of a human being (for example, appearance and voice). The quality of life is integral characteristics of the physical, psychological, emotional, and social functioning of a patient, which is based on his subjective perception. The methods for studying the quality of life include first of all questionnaires that are classified as general and special ones.The general questionnaires are intended to assess the quality of life of both healthy individuals and patients regardless of their disease; the special questionnaires are used to study that in certain categories and groups of patients. The general questionnaires allow the comparison of patients with a population of healthy people. Account must be also taken of the fact that the quality of life varies with age and comorbidities. A great deal of procedures for measuring the quality of life in different groups of people determine whether it is expedient to use the most extensively studied method to adequately assess the findings and to compare with previously performed studies.Examination of changes in the quality of life after saving surgery is a promising line in the study of this disease and may be a success criterion for performed surgical treatment, including palliative care.